Efficiency and applicability of project-based learning in accounting studies - Fortes, Thiago (2020)
This work studied the application of the Project-Based Learning (PBL) methodology to accounting degree in a Higher Education Institution. Considering that PBL provide students with realistic environments and challenges and exposes them to real-world based problems that improve their skills and knowledge in accounting and similar issues. The objective of this study is to measure the effectiveness and applicability of the Project-Based Learning (PBL) method in the Accounting degree at Instituto Politécnico de Bragança, and also highlights the effects on research, questioning, teamwork, problem solving and reallife application of accounting skills, as well as their perception of these skills and the overall satisfaction. The results show that PBL methodology positively enhances students’ capabilities in accounting, while providing them with the opportunity to experience realistic and relevant situations, challenges and problems, albeit with minor hurdles during the completion of the project such as time constraints and workload.